2020
DOI: 10.1371/journal.pmed.1003238
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a city-wide school-located influenza vaccination program in Oakland, California, with respect to vaccination coverage, school absences, and laboratory-confirmed influenza: A matched cohort study

Abstract: BackgroundIt is estimated that vaccinating 50%-70% of school-aged children for influenza can produce population-wide indirect effects. We evaluated a city-wide school-located influenza vaccination (SLIV) intervention that aimed to increase influenza vaccination coverage. The intervention was implemented in �95 preschools and elementary schools in northern California from 2014 to 2018. Using a matched cohort design, we estimated intervention impacts on student influenza vaccination coverage, school absenteeism,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
26
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 60 publications
4
26
1
1
Order By: Relevance
“…We previously reported results from an evaluation of a city-wide SLIV program delivered in elementary schools in Oakland, California from 2014-2018. 20 We found that the intervention was associated with 7-11 percentage points higher vaccination coverage among school-aged children and 17 to 37 lower incidence of influenza hospitalizations per 100,000 during influenza seasons in which a moderately effective vaccine was being used. Here, we investigated whether SLIV effectiveness varied by race/ethnicity in a pre-specified subgroup analysis.…”
Section: Prior Community-based Interventions Increased Influenza Vaccination Coverage Amongmentioning
confidence: 76%
See 4 more Smart Citations
“…We previously reported results from an evaluation of a city-wide SLIV program delivered in elementary schools in Oakland, California from 2014-2018. 20 We found that the intervention was associated with 7-11 percentage points higher vaccination coverage among school-aged children and 17 to 37 lower incidence of influenza hospitalizations per 100,000 during influenza seasons in which a moderately effective vaccine was being used. Here, we investigated whether SLIV effectiveness varied by race/ethnicity in a pre-specified subgroup analysis.…”
Section: Prior Community-based Interventions Increased Influenza Vaccination Coverage Amongmentioning
confidence: 76%
“…11 By increasing vaccination coverage, SLIV may contribute to herd immunity and reduce influenza transmission community-wide, which may reduce racial/ethnic disparities in influenza 12,13 . Prior studies reported that SLIV programs were associated with increased influenza vaccination coverage [14][15][16][17][18][19][20] and decreased school absences [14][15][16][17][20][21][22] and student illness [14][15][16][17] , but no studies have measured the differential impacts of large-scale SLIV interventions by race/ethnicity. We previously reported results from an evaluation of a city-wide SLIV program delivered in elementary schools in Oakland, California from 2014-2018.…”
Section: Prior Community-based Interventions Increased Influenza Vaccination Coverage Amongmentioning
confidence: 99%
See 3 more Smart Citations